Kemampuan Menulis Teks Argumentasi Mahasiswa dengan Metode WH-Questions - Hasibuan, Siti Aminah; Tarigan, Fatin Nadifa (UNIB Press, 2022)
The objective of this study was to find out whether WH - Questions had a significant effect on students' ability to write argumentative text. The subjects of this study were 40 students of the English Education Study Program Universitas Pembinaan Masyarakat Indonesia who were randomly selected. This type of research was experimental research with two groups of students as samples, one as the experimental group and one as the control group. Data collection was carried out using a writing test and analyzed using a t-test. The results showed that the average writing ability of the experimental group was 77.25 and was included in the good category. The average of students who were taught to write argumentation texts using WH - Questions was 77.25, the average of students who were taught to write argumentation texts without WH - Questions was 67.75. It can be seen from the final results of the t-test analysis which states that the t-count value is higher than t-table (5.5599 > 0.320). There were differences in students' writing skills in writing argumentation texts between students who were taught using the WH - Questions and those who did not use the WH - Questions strategy. After analyzing the data, it was found that the students' writing ability in the experimental class was better than the control class.